Optimized modelling of Gaia–Hipparcos astrometry for the detection of the smallest cold Jupiter and confirmation of seven low-mass companions. Issue 2 (3rd August 2021) - Feng, Fabo; Butler, R Paul; Jones, Hugh R A; Phillips, Mark W; Vogt, Steven S; Oppenheimer, Rebecca; Holden, Bradford; Burt, Jennifer; Boss, Alan P
ABSTRACT: To fully constrain the orbits of low-mass circumstellar companions, we conduct combined analyses of the radial velocity data and the Gaia and Hipparcos astrometric data for eight nearby systems. Our study shows that companion-induced position and proper motion differences between Gaia and Hipparcos are significant enough to constrain orbits of low-mass companions to a precision comparable with previous combined analyses of direct imaging and radial velocity data. We find that our method is robust to whether we use Gaia Data Release 2 or Gaia Early Data Release 3, as well as whether we use all of the data or just proper motion differences. In particular, we fully characterize the orbits of HD 190360 b and HD 16160 C for the first time. With a mass of 1.8 ± 0.2  M Jup  and an effective temperature of 123–176 K and orbiting around a Sun-like star, HD 190360 b is the smallest Jupiter-like planet with well-constrained mass and orbit, belonging to a small sample of fully characterized Jupiter analogues. It is separated from its primary star by 0.25 arcsec and thus may be suitable for direct imaging by the coronagraph instrument of the Roman Space Telescope .